THE IMPLEMENTATION OF SOCIAL MEDIA-BASED DIGITAL MARKETING IN NY'S KITCHEN - Jason Santoso; Lita Christina (Universitas Internasional Batam, 2022)
Ny's Kitchen was founded by Mrs. Anny in 2019. Ny's Kitchen is currently located in Ruko Hang Kesturi, Blok I-2 No. 3A, Batam City, Batam. Ny's Kitchen is engaged in the culinary field that sells various types of food prepared from chicken meat. The development of digital marketing based on social media is currently growing very rapidly. So that digital marketing now has a very important role for any existing business. Currently, there are also many competitors who sell similar foods to Ny's Kitchen. Even nowadays competitors have used social media such as Instagram for promotion purposes. Thus, it is very important to apply Instagram-based digital marketing to Ny's Kitchen. The lack of implementation of the applied marketing strategy will potentially lose the market share owned by Ny's Kitchen. The strategies that will be used in promoting Ny's Kitchen are advertising and direct marketing. The implementation of the marketing strategy is expected to increase the sales of Ny's Kitchen.